2018
DOI: 10.3747/co.25.3995
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Patient-Reported Outcomes to Improve Cancer Care in Canada: An Analysis of Provincial Survey Data

Abstract: Patient-reported outcomes measures (proms) are an important component of the shift from disease-centred to person-centred care. In oncology, proms describe the effects of cancer and its treatment from the patient perspective and ideally enable patients to communicate to their providers the physical symptoms and psychosocial concerns that are most relevant to them. The Edmonton Symptom Assessment System-revised (esas-r) is a commonly used and validated tool in Canada to assess symptoms related to cancer. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…This approach can improve efficiency, making it easier to integrate required screening and assessments into the clinical routine. Furthermore, E-health tools potentiate early identification and provide a more dynamic approach to patient-centered care by enabling and encouraging active patient participation [2,3]. In fact, Chrischiles et al found that among the general population, high-frequency users had higher odds of recognizing symptoms and adverse effects among users ≥ 65 years of age [4].…”
Section: Introductionmentioning
confidence: 99%
“…This approach can improve efficiency, making it easier to integrate required screening and assessments into the clinical routine. Furthermore, E-health tools potentiate early identification and provide a more dynamic approach to patient-centered care by enabling and encouraging active patient participation [2,3]. In fact, Chrischiles et al found that among the general population, high-frequency users had higher odds of recognizing symptoms and adverse effects among users ≥ 65 years of age [4].…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of PROMs is well-established 20 - 22 as they allow patients to better communicate their physical and psychosocial symptoms, and promote a shift from disease-centered care to person-centered care. 23 FACT-L is commonly used in research studies and provides a rigorous description of overall quality of life (QoL) across several domains that mirrors problems commonly experienced by people with lung cancer. 24 The MYCaW was developed for use in people with cancer and is most often used in integrative care centres.…”
Section: Discussionmentioning
confidence: 99%
“…23 Current in-person practice in oncology programs using the Edmonton Symptom Assessment Scale (ESAS) and related practice guidelines including COSTaRS is to target clients scoring 4 or higher out of 10 as an indicator of further assessment required. 25,26 Therefore, we used this as the trigger for conducting a COSTaRS symptom assessment. If there were multiple symptoms, nurses started with the highest score or used their judgment as described earlier.…”
Section: Discussionmentioning
confidence: 99%